Widespread domain-like perturbations of DNA methylation in whole blood of Down syndrome neonates - Henneman, Peter; Bouman, Arjan; Mul, Adri; Knegt, Lia; van der Kevie-Kersemaekers, Anne-Marie; Zwaveling-Soonawala, Nitash; Meijers-Heijboer, Hanne E. J.; van Trotsenburg, A. S. Paul; Mannens, Marcel M. (PloS one, 2018)
Down syndrome (DS) is the most frequent genetic cause of intellectual disability. Despite the fact that more than 50 years have passed since the discovery of its genetic aberrations, the exact pathogenesis of the DS phenotype has remained largely unexplained. It was recently hypothesized that the DS pathogenesis involves complex (epi)genetic, molecular and cellular determinants. To date, many reports have addressed epigenetic aberrations associated with DS at different developmental stages/ages and tissue types, but to our best knowledge not in DS newborns. This study aimed to investigate genome-wide methylation patterns in DS newborns compared to non-trisomic newborns. We analyzed blood samples obtained from ten newborns with DS and five age-matched non-trisomic newborns. Epigenetic profiles were obtained from extracted DNA using the Illumina Infinium 450K array. Since aberrant blood cell distribution is known to be present in DS, we applied two distinct models: with and without correction for estimated blood cell distribution. Differentially methylated position (DMP) analysis of the uncorrected model detected 19525 significant hits (51,2% hypomethylated). In the corrected model, we found 121953 significant DMPs (49,8% hypomethylated). Independent of the used model we observed a chromosome 21 dosage effect. Moreover, we detected 46 and 145 differentially methylated regions in the uncorrected and corrected model respectively, both showing hypomethylation overrepresentation. Replication analyses of DMPs and DMRs found by Bacalini et al. (2015) showed a large overlap. In this study, we found methylation profile differences between DS newborns and controls reflecting a systematically affected epigenetic profile. The observed chromosome 21 dosage effect suggests the involvement of affected essential regulatory factors/regions or altered expression of chromatin modeling enzymes located on chromosome 21. Additional research is necessary to substantiate these hypotheses.